Diseño y construcción de un elevador hidráulico para facilitar el ingreso de personas de movilidad reducida de hasta 100 kg de peso a piscinas de recreación - Armas Bustillos, Jairo Amílcar (2016)
In Ecuador 49% of disabled people suffer from physical disabilities, denying the practice of one of the most complete sports is swimming, the inclusion of these people to the sport will be the challenge of this project. The hydraulic elevator for the entry and exit of the pool for the disabled is one of the solutions that make life easier for these people, with full autonomy for handling, for extra safety can also use pregnant or elderly. The materials used in the construction of equipment are stainless steel and duralon, have been selected to have as main property a high resistance to corrosion and they will be in permanent contact with the water and pool chlorine. This equipment has been designed to mobilize the user from the beach to the pool to the glass of the same, using only the pressure of public water service without contaminating the pool or its plant. The total cost of the hydraulic elevator to facilitate the entry of disabled people up to 100 kgf weight recreational pools is USD 2444.84.